Respon Kefir Teh Pegagan Sebagai Minuman Kesehatan - Pramita Laksitarahmi Isrianto (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
Indonesia's local wisdom in utilizing medicinal plants for traditional medicine is very diverse and needs to be preserved. Potential development Centella asiatica (L), that in Indonesia is mostly known as Pegagan, into a healthy drink is often used in the form of a tea bag. However, there is another form that can be used is water kefir. Water kefir is a probiotic drink that contains good bacteria for body immunity. This study aims to determine the Centella asiatica (L)’s kefir response on the chemical and microbiological quality as a probiotic drink. The chemical quality observed were pH, polyphenols, acetic acid, sugar, while the microbiological test used the total LAB (Lactic Acid Bacteria) and total yeast. The design used in this study was a completely randomized design (CRD) with 4 levels of treatment, namely: pegagan tea concentrations of 0%, 15% and 25% with a fermentation time of 12 hours and 24 hours. The research data showed a significant effect between treatments on pH, total polyphenols, total acetic acid, and total sugar with p value = 0.00. The total yield of LAB 1.956 x107 CFU / mL and total Yeast 1.532 x 107 CFU / mL at k concentration of 15% Centella asiatica (L)’s kefir with 24 hours fermentation.